(untitled) (Third Sector Social Economic Review, 2024)
The aim of this study is to examine the effects of university students’ intolerance to uncertainty and social support levels on the perseverance. In the present day, when uncertainty about the future is increasing, intolerance of uncertainty, perseverance and social support concepts come to the fore as important factors. As long as the individual can successfully manage the uncertainty process and tolerate the unknowns, they can keep their communication with people alive, share their feelings and thoughts and get support from the people around them. Individuals who do not give up and who can tolerate uncertainties can gain priority over other individuals in their careers. The sample of the study includes 223 university students studying at Aksaray University Department of Emergency Aid and Disaster Management. When the literature is analysed; although there are a few studies investigating the relationships between the concepts of intolerance of uncertainty social support and perseverance there is no research on the role of intolerance of uncertainty and social support levels on perseverance. According to the findings, no significant relationship was found between intolerance of uncertainty prospective and inhibitory anxiety, which are sub-dimensions of intolerance of uncertainty and perseverance. A significant relationship was found between social support and perseverance. Firstly, it is aimed to provide an applied study to the literature by starting from the researches in the literature on the concepts of intolerance of uncertainty, social support and perseverance.